Evaporation dynamics of a sessile milk droplet placed on a hydrophobic surface - Pathak B.; Christy J. (My University, 2025)
A colloidal droplet is an integral part of spray-drying based applications such as food, pharmaceuticals, drug delivery, etc. The complex physico-chemical dynamics determine the final structures obtained in the process. Therefore, a complete understanding of the different forces involved and the evaluation of the governing parameters is crucial to control the final morphologies as desired. The evaporation-induced dynamics are studied in milk droplets placed on hydrophobic substrates under natural drying condition. Experiments were performed systematically by varying the initial concentration of protein (BSA) in the droplets. The results were analyzed using energy-based models. Capillary forces and inter-particle interaction are found to have dominating effects upon the particle deposition in the evaporating droplets. Furthermore, inclusion of protein beyond a threshold initial concentration leads to buckling instability which produces cavitated structures. Maintenance of hydrophobicity for a sufficient amount of time is an important criterion to initiate the buckling instability. Our study provides physical insights into the dynamics involved in desiccating droplets, including the buckling dynamics. These insights have far-reaching implications in spray-based industries. © 2023 Elsevier B.V.